Immunogenicity of Hydrolysate Formulas in Children (Part 1). Review of 202 Reactions - Arnaldo Cantani (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
Cow's milk (CM) protein hydrolyzed formulas (HFs) appeared in the 40's with the aim of decreasing or eliminating the allergenicity of CM proteins, and in addition of red¬ucing the risk of sensitization. In recent years the so-called "hypoallergenic" (HA) formulas have been devel¬oped. The use of such HFs is based on the premise that predi¬gested pro¬teins, when fed as amino acids and peptides, provide nutrients in a not antigenic form. Thus, pro¬tein HFs have been classified as HA. These formulas are pro¬ces¬sed by heat and enzymatic hydrolysis, and the conforma¬tional and se¬quential structu¬res are more or less changed. The formulas contain pep¬tides of lower molecular wei¬ght (MW) than the nati¬ve protein source, which are thought to be less immuno¬genic. HFs appear to be nu¬triti¬onally adequate and infants gen¬erally gain weight until they refuse the formu¬labe¬cause of its bad taste. However, caution should be taken when such formulas are given for prolonged peri¬ods since no data is available on nutritio¬nal assessment of in¬fants ex¬clusively fed HFs for several months. In this paper we report and discuss > 202 re¬actions to different HFs, including cases of anaphylactic shock and of apparent life-threatening events. The cross-reactivity betw¬een dif¬ferent HFs and CM proteins,and the potential immunoge¬n¬icity of such for¬mulas are dis¬cussed. We con¬clude that none of the HFs are non-aller¬genic, both for al¬lergic children and for high-risk (HR) babies. Moreover we suggest that double-blind placebo-con¬trolled food challenges (DBPCFC) stud¬ies in larger cohorts of babies valuat¬ed with well-defined and -val¬idateddiag¬nos¬tic methods may establish a more reliable prevalence of HF allergy.